Screening tests for N sorption allow to select and engineer biochars for N mitigation during biomass processing. (1st January 2023) - Viaene, J.; Peiren, N.; Vandamme, D.; Lataf, A.; Cuypers, A.; Jozefczak, M.; Amery, F.; Vandecasteele, B.
Highlights: Biochars were tested both for NH4 + -N and NH3 sorption. Both tests enable to select biochars to use in processes for N mitigation. NH4 + -N sorption was higher for manure-based biochars. NH3 sorption showed a positive linear relationship with NH4 + -N sorption. Abstract: Biochar amendment during biomass processing can improve those processes and products, and reduce the emissions of greenhouse gases and NH3, resulting in ecologic and economic benefits. The potential positive effects of biochar are related to NH4 + -N and NH3 sorption, which in turn are depending on different biochar characteristics. By knowing the relationship between biochar characteristics and NH4 + -N and NH3 sorption, biochar production can be steered towards a higher N sorption or existing biochars can be selected for targeted applications for high N sorption. Therefore, this study aims to develop fast screening tests to estimate the potential for both NH4 + -N and NH3 sorption of biochar, before application in biomass processing. Further, the effects of feedstock, pyrolysis temperature, biochar characteristics and biochar treatments on N sorption are studied. The results show that NH4 + -N sorption varied between 0 and 1.54 mg NH4 + -N/g fresh biochar and was highest for manure-based biochars with a high nutrient content and cation exchange capacity, produced at lower temperatures (300–450 °C). For some biochars, the feedstock itself had a higher NH4 + -N sorption than the biochar. Grinding and washing increased the NH4 + -N sorption. In addition, a general linear model was proposed to predict the NH4 + -N sorption based on three chemical characteristics· NH3 sorption varied between 0 and 100 % of the negative control and showed a linear positive relationship with the NH4 + -N sorption, moisture retention factor and cation exchange capacity. Pyrolysis temperature and feedstock type did not significantly affect NH3 sorption. NH4 + -N and NH3 desorption varied amongst biochar type.